New Insights on the Neglected Avian Nematode Hystrichis tricolor: Hystrichiosis-Induced Proventriculitis in Synanthropic Egyptian Geese (Alopochen aegyptiaca Linnaeus, 1766) in Germany - Fischer, Ella F.; Schlohsarczyk, Elfi K.; Gröf, Manuela; Gärtner, Ulrich; Taubert, Anja; Hermosilla, Carlos; Justus Liebig University Giessen (My University, 2023)
Hystrichis tricolor is a neglected avian enoplid nematode (superfamiliy Dioctophymatoidea) and known to parasitize various species of the Anatidae (Anas spp. and Mergus spp.) from the northern hemisphere, inducing mainly proventriculitis in domestic and wild waterfowl. Here, we focus on the pathological findings of naturally H. tricholor-infected Egyptian geese (Alopochen aegyptiaca) and a neozoan shelduck (Tandorninae) of Germany. Nowadays, this species is considered the fastest-spreading alien waterfowl species withinWestern Europe. Additionally, molecular sequencing coupled with phylogenetic characterization of H. tricolor is reported. Post mortem analyses unveiled patent gastric H. tricolor infections in eight of twelve infected birds (8/12; 66.7%), inducing proventriculitis resulting in large visible nodular lesions. Histopathological findings point to chronic host pro-inflammatory immune reactions. These results demonstrate the potential role of Egyptian geese as natural reservoir hosts of H. tricholor and highlight their possible role in parasite transmission (i.e., spillback) into endemic waterfowl species. Due to avian health concerns, the occurrence of hystrichiosis should be monitored in native waterfowl in the future, introducing appropriate management practices in conservation strategies of endemic wild birds not only in Germany but elsewhere in Europe.
Keywords: Hystrichis tricolor; Alopochen aegyptiaca; endoparasites; Egyptian goose; proventriculus; ddc:630